Technology Neutrality in European Regulation of GMOs. Issue 1 (2nd January 2022) - Sandin, Per; Munthe, Christian; Edvardsson Björnberg, Karin
ABSTRACT: Objections to the current EU regulatory system on genetically modified organisms (GMOs) in terms of high cost and lack of consistency, speed and scientific underpinning have prompted proposals for a more technology-neutral system. We sketch the conceptual background of the notion of 'technology neutrality' and propose a refined definition of the term. The proposed definition implies that technology neutrality of a regulatory system is a gradual and multidimensional feature. We use the definition to analyze two regulatory reform proposals: One proposal from the Netherlands for improving the exemption mechanism for GMOs under Directive 2001/18/EC, and one from the Norwegian Biotechnology Advisory Board, outlining a new stratified risk assessment procedure. While both proposals offer some degree of improved technology neutrality in some dimensions compared to current EU regulation, in some extents and dimensions, they do not. We conclude that proposals for more technology-neutral regulation of GMOs need, first, to make explicit to what extent and in what dimensions the proposal improves neutrality and, second, to present arguments supporting that these specific improvements constitute desirable policy change against the background of objections to current policy.